Divergence in response of lettuce (var. ramosa Hort.) to copper oxide nanoparticles/microparticles as potential agricultural fertilizer. Issue 1 (1st January 2019) - Wang, Yujing; Lin, Yijie; Xu, Yanwen; Yin, Ying; Guo, Hongyan; Du, Wenchao
ABSTRACT: CuO particles can be used as an agrochemical with slow and controlled release of micronutrients but, their size-specific effects have not been well elucidated. In this study, soil-grown lettuce was exposed to CuO nanoparticles ( n CuO) and CuO microparticles ( μ CuO) at 0, 200, and 400 mg Cu/kg for 60 days. At harvest, n CuO released 82.2% and 117.7% more Cu ions, as well as 48.7% and 75.3% more DTPA-extractable Cu than μ CuO at 200 and 400 mg/kg, respectively. CuO treatments induced higher copper accumulated in lettuce roots but did not change shoot's Cu content or cause oxidative stress. n CuO treatments increased shoot's biomass by 16.3–19.1%, while μ CuO showed no improvement to the biomass. The beneficial effects on lettuce by n CuO may be attributed to its modification in plant photosynthesis system with increased transpiration rate and higher stomatal conductance. Results indicate that n CuO can be a promising agrochemical fertilizer to increase crop production.